Prediction of Hepatic Complications after Allogeneic Haemotopoetic Stem Cell Transplantation Using Liver and Spleen Stiffness Measurement - Franke, Georg-Nikolaus; Weiße, Tina; Petroff, David; Beer, Sebastian; Döhring, Christine; Behre, Gerhard; Fischer, Janett; Lindner, Franziska; Wiegand, Johannes; Keim, Volker; Niederwieser, Dietger; Karlas, Thomas (Blood, 2018)
Rationale: Allogeneic haematopoietic stem cell transplantation (HCT) is the only curative option for a variety of malignant and non-malignant diseases and is increasingly used, even in elderly and medically unfit patients (pts). Despite advances, it is associated with considerable morbidity and mortality. Major obstacles to a successful outcome are infections and graft-versus-host-disease (GvHD) but also liver-related complications like sinusoidal obstruction syndrome (SOS). An important risk factor is a preexisting chronic liver disease. Screening includes hepatitis serology and PCR, ultrasound of the liver and liver related laboratory evaluations of transaminases, gamma-GT and bilirubin. Liver stiffness measurements (LSM) using point shear-wave elastography (pSWE) and transient elastography (TE) have emerged as non-invasive methods to detect hepatic fibrosis. In addition, controlled attenuation parameter (CAP) has good accuracy for detection and differentiation of histologically defined steatosis. Both methods have been extensively evaluated in patients with various chronic liver diseases and represent non-invasive alternatives to liver biopsy. Preliminary reports suggest a potential prognostic role for LSM in the HCT setting. Patients and Methods: Consecutive pts who underwent HCT for malignant or non-malignant diseases underwent ultrasound, liver elastography and non-invasive liver fat quantification by CAP before and post conditioning. Cut-off values of 7 kPa (LSM), 1.34 m/s (pSWE), and 248 dB/m (CAP) were defined for hepatic fibrosis and steatosis, respectively. Additionally, PNPLA3 genotyping was performed. The results were correlated with the clinical course of the pts with an observation time post-HCT of 100 days. In addition overall survival (OS) and disease relapse at one year were recorded as exploratory endpoints. Events were defined as SOS, GvHD grade II-IV, sepsis from any cause, or death. Severe liver related events were either SOS, GvHD of the liver stage 3-4, or drug induced liver injury (DILI). Competing risk models and Cox regression were used for analysis. Results: Of the 120 pts screened for the trial, 110 proceeded to receive an HCT. 4 pts were excluded from the analysis because of invalid elastography. PNPLA3 genotyping was available in 103 pts. 106 pts (median age 57 years (y), 42 females, median body mass index 24.6 kg/m²) were transplanted from a matched or mismatched unrelated (n=84) or sibling donor (n=22) for acute leukemias (n=52), lymphoma or multiple myeloma (n=19), MDS/MPN (n=31) or other diseases (n=4) using myeloablative (n=27), reduced intensity (n=23) or non-myeloablative conditioning (n=56) between 2014 and 2016. A total of 33 pts developed severe complications: non-hepatic events were sepsis in 12 pts and GvHD in 5 pts. Liver-related complications occurred in 16 pts (6 female, median age 60.5 y): n=9 SOS, n= 5 liver GvHD, and n=2 DILI. The hazard ratio was 3.2 (p = 0.0022) for patients with LSM > 7 kPa and 4.4 (p = 0.0042) with pSWE > 1.34 m/s . An analysis with SOS as an endpoint was not possible due to low incidence. However, within the subgroup with liver events (n=16) the 9 patients with SOS had higher LSM values (8.2 vs 4.6 kPa, p=0.031) and showed a trend toward higher pSWE values (1.67 vs 1.29 m/s, p=0.087). GGT at baseline differed significantly between pts with liver events and those without (p=0.020). Combining GGT > 1x ULN and LSM > 7 kPa the hazard ratio was 10.8 (p=0.0097). Pts with elevated LSM at baseline had a trend toward higher non-relapse mortality (p=0.070) and had significantly lower OS at 1 y after HCT (p=0.0038). Gender, age, type of conditioning, busulphane containing conditioning, diagnosis, HCT-CI score, CAP, and PNPLA3 genotype showed no impact on the development of severe complications or liver events, however prior stem cell therapy was strongly associated with outcome. Conclusions: Elevated liver stiffness assessed by either TE or pSWE is associated with an increased risk for liver related complications including SOS, non-relapse mortality and decreased survival after allogeneic HCT. LSM should be evaluated further as a potential additional prognostic marker in the comorbidity assessment before transplant. Pts at higher risk for liver related events could be subject to additional prophylaxis such as defibrotide for the prevention of SOS. Franke:Novartis: Consultancy, Honoraria, Research Funding; Pfizer: Consultancy; Jazz: Honoraria. Niederwieser:Miltenyi: Speakers Bureau; Novartis: Research Funding.